1998
DOI: 10.1097/00006534-199801000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Microvascular Anastomosis in the Neck

Abstract: Structural and morphometric investigations of the vessels of the neck region were carried out on 30 cadavers (15 male and 15 female in the age range of 45 to 93 years old) to gain more knowledge of the anatomy for microvascular surgery. Our results briefly are as follows: (1) The non-common-truck type of the external carotid artery (in which each branch arises separately from the external carotid artery) was found in 76.6 percent of cases, the truncus linguofacialis type was found in 21.7 percent, and the trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 10 publications
1
34
0
1
Order By: Relevance
“…22 Another critical element of surgical planning is the identification of anatomic variants (Table and Fig 5). 24 Both arteries and veins can have a common trunk, leading to larger caliber vessels compared with the smaller individual vessels. Larger caliber trunks are considered more favorable because the anastomosis is simpler and safer.…”
Section: Selection Of Recipient Vesselsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Another critical element of surgical planning is the identification of anatomic variants (Table and Fig 5). 24 Both arteries and veins can have a common trunk, leading to larger caliber vessels compared with the smaller individual vessels. Larger caliber trunks are considered more favorable because the anastomosis is simpler and safer.…”
Section: Selection Of Recipient Vesselsmentioning
confidence: 99%
“…Seventeen percent of individuals have dupli- cated external jugular veins, and 30% of individuals have duplicated anterior jugular veins. 24 As a general rule, 2 venous anastomoses are used to maintain sufficient outflow. Conventional thinking is that compared with the corresponding arteries, selection of drainage veins is considered less critical.…”
Section: Selection Of Recipient Vesselsmentioning
confidence: 99%
“…The diameters of cervical blood vessels used as feeding arteries during vascularized free-flap grafting after malignant-tumor resection have been reported sporadically 38,39) . To our knowledge, however, no previous study has measured the luminal diameters of the main trunk of the maxillary artery and its branches.…”
Section: Luminal Diameters Of Branches Of the Maxillary Arterymentioning
confidence: 99%
“…Superficial venous system is EJV which is formed by union of posterior division of retromandibular vein and posterior auricular vein and runs downward over sternocleidomastoid (SCM) muscle, reaches the roof of posterior triangle and pierces the investing layer of deep cervical fascia and drains into ipsilateral subclavian vein [1]. Shima et al [2] reported 17 % incidence of double EJV where it begins as two veins and joins at the posterior aspect of SCM caudally. Anatomical course of EJV and relationship to the adjacent stable and predictable landmark is important and this knowledge is important in various clinical scenarios.…”
Section: Introductionmentioning
confidence: 99%